Commuting, migration and local employment elasticities - Monte, Ferdinando; Redding, Stephen; Rossi-Hansberg, Esteban (London, 2015)
"Many changes in the economic environment are local, including policy changes and infrastructure investments. The effect of these changes depends crucially on the ability of factors to move in response. Therefore a key object of interest for policy evaluation and design is the elasticity of local employment to these changes in the economic environment. We develop a quantitative general equilibrium model that incorporates spatial linkages between locations in goods markets (trade) and factor markets (commuting and migration). We find substantial heterogeneity across locations in local employment elasticities. We show that this heterogeneity can be well explained with theoretically motivated measures of commuting flows. Without taking into account this dependence, estimates of the local employment elasticity for one location are not generalizable to other locations. We also find that commuting flows and their importance cannot be accounted for with standard measures of size or wages at the county or commuting zone levels."